2018
DOI: 10.5296/gjes.v4i1.13226
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Curiosity Experiences Among Tertiary Students

Abstract: Curiosity is a motivation construct that is important at all levels of education. This study investigated the curiosity experiences of tertiary students. Individual interviews were carried out with 20 tertiary students. Participants were asked to describe experiences of wanting-to-learn (positive curiosity) or not-wanting-to-learn (negative curiosity) that they had recently experienced in regular classes. Participants reported they had recently experienced both forms of curiosity, which correlated with high an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…They investigated the antecedents of curiosity from a self-determination theory perspective and found teacher support and peer in uence affected high school students' curiosity in using the Internet. Palmer (2018) found that personal interest in the topic and the interesting elements of the lesson were the main in uencing factors of curiosity among tertiary students. This line of inquiry needs pursuing further, particularly in the area of language learning.…”
Section: Introductionmentioning
confidence: 94%
“…They investigated the antecedents of curiosity from a self-determination theory perspective and found teacher support and peer in uence affected high school students' curiosity in using the Internet. Palmer (2018) found that personal interest in the topic and the interesting elements of the lesson were the main in uencing factors of curiosity among tertiary students. This line of inquiry needs pursuing further, particularly in the area of language learning.…”
Section: Introductionmentioning
confidence: 94%
“…Subsequently, the perceived value was found to be relevant also in the case of epistemic emotions. For example, Palmer (2018) and Rossing and Long (1981) found curiosity positively associated with perceived value. Di Leo et al (2019) noted high task value levels related more to curiosity and less to anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%